Rupture of the Ascending Aorta Surgical Area Detected Using Isolated Cardiopulmonary Organ Computed Tomography Angiography: An Autopsy Case Report After Cardiac Surgery. (September 2021) - Tian, Zhiling; Wang, Zhuoqun; Wan, Lei; Zhang, Jianhua; Dong, Hewen; Liu, Ningguo; Chen, Yijiu
Abstract : Abstract: We report cause of death after cardiac surgery using isolated cardiopulmonary organ computed tomography angiography (CTA) and a conventional autopsy. A 56-year-old man underwent aortic valve replacement and coronary artery bypass graft surgery under extracorporeal circulation. Massive bleeding occurred suddenly, and the patient died 25 days later. An autopsy revealed fibrinous exudate in the mediastinum and tight attachment of the pericardium to the heart; there were also clots and inflammatory exudate in the chest cavity. Separating the organs in the chest cavity was difficult, especially in the surgical area. We extracted the heart and lungs together and performed cardiovascular CTA and image reconstruction. Results showed spillage of the contrast agent from the anterior wall of the ascending aorta, approximately 4.5 cm from the replaced aortic valve. A histological examination confirmed that the site of contrast agent spillage was the sutured area of the ascending aorta, which was infected, necrotic, and had ruptured. Using the CTA approach for isolated cardiopulmonary organ imaging can accurately display the location of an aortic rupture, which further guides organ inspection and tissue sampling, and avoids irreversible damage to key regions. In conclusion, the approach we describe can provide evidence for determining cause of death.